Effectiveness of Surgical Treatment of Rockwood Type III Acromioclavicular Joint Dislocation Using Clavicle Hook Plate and Tension Band Wiring: A Comparative Study to Evaluate the Functional and Surgical Outcome - Shrestha, Dinesh Kumar; Shrestha, Merina; KC, Dipendra; Karki, Prateek; Shrestha, Sabin; Yogi, Sushil (Journal of Nepalgunj Medical College, 2020)
Introduction: Acromioclavicular joint dislocation Type III is still controversial for its management, despite of numerous trials and reviews. Aims: To compare and evaluate the functional and surgical outcome of Rockwood Type III acromioclavicular joint dislocation treated surgically with clavicular Hook plate and Tension Band wiring with K-wires. Methods: In a prospective hospital based interventional study comprising of total 22 patients with a mean age of 31.36 ± 7.53 years who presented with Rockwood Type III acromioclavicular joint dislocation were carried between January 2018 to December 2019. They were graded according to Rockwood et al. classification. All 22 patients underwent open reduction and internal fixation. These patients were divided into two groups according to operative procedure; of which 11 patients were treated with clavicular hook plate (CHP) and rest 11 were treated with tension band wiring with K-wires (TBW). Descriptive comparison was tabulated during pre-operative, intra-operative and post-operative periods. The Constant-Murley Shoulder scoring system was applied for evaluating the results. Results: The mean follow up period was 7.6 months. The clavicular hook plate was removed at 10 months in one patient due to severe pain and limited range of motion , and removal of Tension Band wiring with K-wires were done in two patients due to wound dehiscence and Kirschner wire back out at 5 and 6 months. The mean Constant- Murley shoulder score was 82.6 (min. 70 & max. 93) in clavicular hook plate and 74.72 (min 68 & max. 84) in Tension band wiring with K-wires which found to be significantly difference in mean scoring between two groups. Conclusion: Patients treated with Clavicular Hook Plate for Rockwood Type III acromioclavicular joint dislocation had a very good functional and surgical outcome over Tension Band wiring with K-wires.